2020
DOI: 10.3389/fphar.2020.582003
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs Bioinformatics Analyses Identifying HDAC Pathway as a Putative Target for Existing Anti‐COVID‐19 Therapeutics

Abstract: Over 313,000 SARS-CoV-2 positive cases have been confirmed in Italy as of 30 September 2020, and the number of deaths exceeding thirty-five thousand makes Italy among the list of most significantly affected countries in the world. Such an enormous occurrence of infections and death raises the urgent demand for effective available treatments. Discovering the cellular/molecular mechanisms of SARS-CoV-2 pathogenicity is of paramount importance to understand how the infection becomes a disease and how to plan any … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 47 publications
1
24
0
Order By: Relevance
“…Teodori et al . carried out a bioinformatic analysis to show that the HDAC pathway is the key to the pathogenicity of SARS-CoV-2 [ 51 ]. They proposed that activation of AT1R (angiotensin II receptor type 1) by the excessive accumulation of angiotensin II (AngII) leads to the stimulation of HDACs that upregulate ACE2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Teodori et al . carried out a bioinformatic analysis to show that the HDAC pathway is the key to the pathogenicity of SARS-CoV-2 [ 51 ]. They proposed that activation of AT1R (angiotensin II receptor type 1) by the excessive accumulation of angiotensin II (AngII) leads to the stimulation of HDACs that upregulate ACE2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Each miRNA can target multiple messenger RNAs (mRNAs), and altogether, miRNAs are predicted to regulate more than half of the human transcriptome (Friedman et al, 2009). Recent evidence has shown that different diseases, including COVID-19, lead to distinct complements of miRNAs in the blood (Nersisyan et al, 2020;Sac ¸ar Demirci and Adan, 2020;Teodori et al, 2020). These circulating miRNAs are highly stable and have the potential to be used for minimally invasive detection, as biomarkers, and as therapeutic targets (Tribolet et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Many of these docking mechanisms are pH dependent. So far, studies show that SARS-CoV-2 uses the ACE2 receptor as a main docking protein (Yang et al, 2020;Teodori et al, 2020). ACE2 is essential for SARS-CoV-2 fusion, but it is uncertain whether ACE2 interactions are enough for SARS-CoV-2 binding.…”
Section: Increased External Ph May Disadvantage Virus Infectionmentioning
confidence: 99%